2014
DOI: 10.1038/ncomms5393
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol selectively activates canonical Wnt signalling over non-canonical Wnt signalling

Abstract: Wnt proteins control diverse biological processes through β-catenin-dependent canonical signaling and β-catenin-independent non-canonical signaling. The mechanisms by which these signaling pathways are differentially triggered and controlled are not fully understood. Dishevelled (Dvl) is a scaffold protein that serves as the branch point of these pathways. Here, we show that cholesterol selectively activates canonical Wnt signaling over non-canonical signaling under physiological conditions by specifically fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 70 publications
7
111
0
Order By: Relevance
“…Despite the advantages of this probe, it does have the same limitation that applies to all of these types of biosensors, in that they only have access to available lipid. Recent evidence suggests that cholesterol might act as an allosteric regulator for many membrane proteins such as ion channels and scaffolding proteins, which will likely influence the amount of freely accessible cholesterol (Sheng et al, 2012;Levitan et al, 2014;Sheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of this probe, it does have the same limitation that applies to all of these types of biosensors, in that they only have access to available lipid. Recent evidence suggests that cholesterol might act as an allosteric regulator for many membrane proteins such as ion channels and scaffolding proteins, which will likely influence the amount of freely accessible cholesterol (Sheng et al, 2012;Levitan et al, 2014;Sheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One benefit of this methodology is that we can monitor the change of transbilayer distribution of cholesterol in the PM in any physiological events. For example, one of the Wnt ligands, Wnt3a, induced redistribution of cholesterol from the exofacial to cytosolic leaflets of the PM [72,79]. Moreover, ABCA1 and ABCG1, ATP-binding cassette (ABC) transporters, were shown to be essential for maintaining of the low cholesterol concentration in the inner PM in HeLa and HEK293 cells [72,80,81].…”
Section: Cholesterol Biosensors Derived From Perfringolysin O Thetmentioning
confidence: 99%
“…Recent studies have suggested that membrane lipids play a role in modulating cellular protein-protein interactions mediated by another PID, PDZ ( P SD95, D lg1, Z O-1) domain (Chen et al, 2012; Feng and Zhang, 2009; Sheng et al, 2012; Sheng et al, 2014; Wu et al, 2007; Zimmermann et al, 2002). It was also reported that some SH2 domains could bind lipids, which either inhibited (Rameh et al, 1995) or promoted (Bae et al, 1998) the activity of their host proteins; however, the mechanisms, the physiological significance, and the universality of these findings remain controversial (Surdo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%